Development of a User Interface (Front End) in a Website-Based Village Information System to Improve Service Quality and Community Empowerment Information: Sindangresmi Village Information System - Titipan, Muhammad Raga; Virgono, Agus; Hasibuan, Faisal Candrasyah (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2025)
Sindangresmi Village is one of 10 villages in the Jampang Tengah District, Sukabumi Regency. The village is the most accurate data source for searching population data. For this reason, the method of collecting population data, filling in data in a format, and data processing to present population data information to the public must be carried out effectively and efficiently so that the information can be conveyed quickly and accurately. For the case study in this village, the data collection process for services is still manual. Therefore, there are always errors and duplications of data. Because manual data collection is prone to data entry errors, duplication, or loss due to human error. In addition, the difficulty of accessing information is also a problem due to the need for an organized system for storing and managing village data. A website-based village information system has become a promising solution for improving service quality and access to information to empower rural communities. The programming language used to build this system is HTML (Hypertext Markup Language), with the framework PHP (Hypertext Preprocessor) and SQL (Structured Query Language) as the database. Keyword : Village Information System Digitalization Sindangresmi